(untitled) (The International Journal for Scientific Research, 2024)
Study Overview: This is a study of Criticism of the texts of the Prophet’s hadith amongst the Arab Modernist Thought, which derives its ideas from outside the Islamic system of thought. Rather, its more akin to Western understanding regarding religious texts, or more specifically that regarding Theology, with its use and application of modern hermeneutical theories upon the Sunnah and its understanding. Therefore, it differs greatly from Islamic Thought which derives its methodology from Ahlu-Sunnah wal Jama’ah and the Hadith Scholars in its principles and application. Study Aims: The research is concerned with highlight Modernist Thought effects upon the Prophetic Sunnah, and also concerned with studying and analyzing modernist ideas on the subject of Criticism of the texts of the Prophet’s hadith specifically.